2019
DOI: 10.1016/j.meatsci.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies to reduce methane emissions from cattle: Effects on meat eating quality and retail shelf life of loin steaks

Abstract: Increasing the lipid concentration and/or inclusion of nitrate in the diet of ruminant livestock have been proposed as effective strategies to reduce the contribution of methane from the agricultural sector to greenhouse gas emissions. In this study, the effects of increased lipid or added nitrate on beef eating quality were investigated in two experiments. In experiment 1, lipid and nitrate were fed alone with two different and contrasting basal diets to finishing beef cattle. In the second experiment, lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Studies of feeding red seaweed ( Asparagopsis taxiformis ) found that enteric methane emission was reduced, but there was no difference in average daily gain, carcass quality, strip loin proximate analysis, shear force or consumers’ taste preferences [ 64 ]. Nutrient treatments (nitrate and lipid) that reduced methane emissions also did not adversely affect meat qualities such as tenderness, juiciness and so on [ 65 ]. Similary, tannins, known to have antioxidant properties, reduced methane emissions in sheep, but had no effect on Bapedi ram meat sensory attributes [ 66 ].…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…Studies of feeding red seaweed ( Asparagopsis taxiformis ) found that enteric methane emission was reduced, but there was no difference in average daily gain, carcass quality, strip loin proximate analysis, shear force or consumers’ taste preferences [ 64 ]. Nutrient treatments (nitrate and lipid) that reduced methane emissions also did not adversely affect meat qualities such as tenderness, juiciness and so on [ 65 ]. Similary, tannins, known to have antioxidant properties, reduced methane emissions in sheep, but had no effect on Bapedi ram meat sensory attributes [ 66 ].…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…Urea is the main source of non-protein nitrogen (NNP) supplied to ruminants. However, other unconventional sources of NNP, which have a greater reduction in GHG emissions, are being evaluated for commercial use (RICHARDSON et al, 2019).…”
Section: Pasture Cattle Supplementationmentioning
confidence: 99%
“…E as pastagens e o componente arbóreo quando bem manejadas, durante o ciclo de C na fotossíntese podem converter o CO2 atmosférico em massa vegetal (podendo servir de alimento aos animais) e auxiliar na conservação do estoque de C existente no solo (por meio da deposição de material orgânico das perdas de pastejo ou pela morte e deposição de raízes no solo), como no fuste das árvores dos sistemas integrados com pastagens e florestas (TORRES et al, 2017;BOSI et al, 2020a;DOMICIANO et al, 2020). SAKAMOTO (2018), enfatiza que atualmente existem diversas estratégias de mitigação dos GEE na agropecuária e elas consistem em três categorias: 1) aumento da produção animal, com a melhoria dos índices zootécnicos de forma intensiva (CARDOSO et al, 2016;OLIVEIRA et al, 2018); 2) manejo adequado do solo, realizando a implementação de práticas que possibilitem melhorar o valor nutritivo das pastagens com diversas alternativas sustentáveis (DEMARCHI et al, 2016;CARDOSO et al, 2020a); e 3) manejo alimentar, fornecendo alimentos de boa qualidade que irão atuar diretamente na fermentação e nos produtos da fermentação dos ruminantes (RICHARDSON et al, 2019;KOSCHECK et al, 2020), manipulando as intensidades de emissões de GEE dos animais.…”
Section: Emissão De Gases De Efeito Estufa Manejo Da Pastagem E Estra...unclassified
“…Pensando nestes aspectos e nas questões sustentáveis mundiais, além de aumentar a produção alimentícia no Brasil (GREENWOOD, 2021), identificar ingredientes ou alimentos estratégicos que possam reduzir as emissões de GEE sem afetar a produtividade se torna fundamental (RICHARDSON et al, 2019;CARDOSO et al, 2020b;KOSCHECK et al, 2020), principalmente, nos períodos secos e de transição (CARDOSO et al, 2020a;TORRECILHAS et al, 2021). O nitrato de amônio (NH4NO3), especificamente, é um ingrediente fonte de nitrogênio não-proteico (NNP) que atua como uma alternativa para auxiliar na redução da produção individual de CH4 entérico dos animais, fornecendo substrato para os microrganismos metanogênicos (HULSHOF et al, 2012;VELAZCO et al, 2014); além de permitir, de uma forma geral, melhorar a eficiência alimentar dos animais em pastejo por meio da síntese de proteína microbiana e redução da necessidade de fontes de proteína verdadeira, atendendo as necessidades fisiológicas básicas rapidamente (FREIRE et al, 2015;YANG et al, 2016).…”
Section: Desempenho Animal E Uso De Suplementosunclassified